ANALISIS SISTEM PENDIDIKAN KOLONIAL BELANDA DARI POLITIK ETIS HINGGA WARISAN STRUKTUR PENDIDIKAN MODERN - Widya Nur Asyifa (CV. ADIBA AISHA AMIRA, 2026)
The education system in Indonesia is closely related to the history of Dutch colonialism. One of the most influential policies affecting the development of education in the Dutch East Indies was the Ethical Policy implemented in the early twentieth century. This policy emerged as a form of moral responsibility of the Dutch government toward the indigenous population after criticism of colonial exploitation practices. This study aims to analyze the Dutch colonial education system from the implementation of the Ethical Policy to its influence on the structure of modern education in Indonesia. This research uses a qualitative method with a literature study approach. Data were collected from books, journals, and other scientific sources related to the history of Indonesian education. The results show that the Dutch colonial education system had several main characteristics: educational policies influenced by the Ethical Policy, a discriminatory education system based on social status, and the formation of a formal education structure that later influenced the modern education system in Indonesia. Therefore, although colonial education served political and administrative purposes for the Dutch government, it also contributed to shaping the structure of education in Indonesia today.